Sex differences in parent‐reported executive functioning and adaptive behavior in children and young adults with autism spectrum disorder. Issue 10 (1st June 2017) - White, Emily I.; Wallace, Gregory L.; Bascom, Julia; Armour, Anna C.; Register‐Brown, Kelly; Popal, Haroon S.; Ratto, Allison B.; Martin, Alex; Kenworthy, Lauren
Abstract : This study is the largest to date examining executive function and adaptive skills in females with autism spectrum disorder (ASD). Its primary aim was to utilize parent ratings of real‐world executive functioning and adaptive behavior to better understand whether females with ASD differ from males with ASD in these areas of everyday functioning. We compared 79 females with ASD to 158 males with ASD (ages 7–18) who were statistically matched on age, IQ, and level of ADHD or ASD traits. All participants were assessed using the Behavior Rating Inventory of Executive Function (BRIEF) and a subset (56 females and 130 males) also received the Vineland Adaptive Behavior Scales (VABS). Females were rated by parents as having greater problems with executive function on the BRIEF. Parents also rated females as exhibiting more difficulties than males on the Daily Living Skills domain of the VABS. There was a correlation between increased global EF difficulty and decreased adaptive ability in both males and females. Our results indicate relative weaknesses for females compared to males diagnosed with ASD on executive function and daily living skills. These differences occur in the absence of sex differences in our sample in age, IQ, clinician ratings of core ASD symptomatology, parent ratings of ADHD symptoms, and parent‐reported social and communication adaptive skills on the VABS. These findings indicate specific liabilities in real world EF and daily living skills for females with ASD and have important implications for targeting their treatments. Autism Res 2017, 10: 1653–1662 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.